2015
DOI: 10.1074/jbc.m115.638759
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Trimming of Cell Surface Polysialic Acid (PolySia) by Exovesicular Sialidase Triggers Release of Preexisting Surface Neurotrophin

Abstract: Background:Although polySia is known to retain neurotrophins, their releasing mechanism remains unknown. Results: PolySia present on the cell surface of microglia is rapidly cleared by Neu1 sialidase on exovesicles secreted upon inflammatory stimulus, leading to neurotrophin release. Conclusion: Exovesicular Neu1 regulates rapid turnover of polySia and concomitant neurotrophin function. Significance: First demonstration of on-site turnover of polySia and its physiological significance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
85
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 83 publications
(88 citation statements)
references
References 55 publications
3
85
0
Order By: Relevance
“…Thus, Neu5Gc is incorporated into NCmahTg polySia as well as Neu5Ac, and yet apparently it results in no gross defect in brain development. Of course, this does not rule out the possibility that neuronal development might be affected at the cellular level or that the release of brain-derived neurotrophic factor or growth factors bound on polySia might be impaired (19).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, Neu5Gc is incorporated into NCmahTg polySia as well as Neu5Ac, and yet apparently it results in no gross defect in brain development. Of course, this does not rule out the possibility that neuronal development might be affected at the cellular level or that the release of brain-derived neurotrophic factor or growth factors bound on polySia might be impaired (19).…”
Section: Resultsmentioning
confidence: 99%
“…PolySia modulates cell-cell interactions, thus playing important roles in neuronal development and regeneration (15)(16)(17). Recently, it was suggested that polySia also serves as a reservoir of growth factors (18,19). Genetic studies have revealed that variation in a gene encoding the enzyme that biosynthesizes polySia, ST8SIA2, could be a risk factor of psychiatric disorders such as schizophrenia, autism spectrum, and bipolar disorder (20 -23).…”
mentioning
confidence: 99%
“…Desialylation on the cell surface by sialidase can change cell surface properties quickly and dramatically. Neu1 is also contributed to the desialylation on the cell surface in the central nervous system [11]. Neu3, plasma-membrane-bound sialidase, cleaves sialic acid bound to the major brain gangliosides that are necessary for memory function.…”
Section: Discussionmentioning
confidence: 99%
“…Since exogenous sialidase extracellularly applied to the hippocampus influences memory and synaptic plasticity [9, 10], endogenous sialidase activity in the extracellular space would also affect the hippocampal memory processing. In the case of inflammatory response in the central nervous system, sialylation level with PSA on microglial cells was regulated by exovesicular sialidase [11]. Mammalian sialidase isozymes are designated as Neu1, Neu2, Neu3 and Neu4.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation